Peningkatan Kemampuan Menjadi Mc Pada Acara Resepsi Pernikahan Melayu Riau Pada Siswa SMA Negeri 7 Kecamatan Senapelan Kota Pekanbaru - Amanan; Hermansyah; Juswandi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2024)
The Master of Ceremony (MC) is a professional event host responsible for guiding and entertaining various events. The MC plays a crucial role in ensuring that events, ranging from formal activities to weddings, run smoothly according to the predetermined schedule provided by event organizers and protocol officers. In addition to this, the MC is tasked with thoroughly understanding the event, as directed by the event organizer. This community service program is organized for the students of SMA Negeri 7 in Senapelan District. Recognizing the significance of fostering and developing Malay culture and the Malay (BMR) region, the Riau Provincial Government has initiated programs in line with the reform era. The primary objective of this program is to enhance the students' abilities to become proficient and professional MCs. The event will focus on interpreting, training, and practicing the art of being an effective MC, particularly for Riau Malay Wedding Receptions.The program aims to contribute to the improvement of MC skills, providing valuable assistance to the students of SMA Negeri 7 in Senapelan District, Pekanbaru. The visiting team from the Faculty of Cultural Studies at Universitas Lancang Kuning is expected to aid the school and its students in understanding Riau Malay culture, with a specific focus on improving MC capabilities for Riau Malay Wedding Receptions. In today's era, those who possess a strong understanding of this field are taking significant strides, and the demand for professionals in this domain is on the rise.